2018
DOI: 10.1021/acs.inorgchem.8b03116
|View full text |Cite
|
Sign up to set email alerts
|

Facile and Massive Aluminothermic Synthesis of Mayenite Electrides from Cost-Effective Oxide and Metal Precursors

Abstract: Subnanoporous mayenite electride [Ca 24 Al 28 O 64 ] 4+ (O 2− ) 2−x (e − ) 2x (C12A7:e − ) as the first room temperature-stable inorganic electride has attracted intensive attention because of its fascinating chemical, electrical, optical, and magnetic properties. However, it usually needs to be synthesized through a complicated multistep process involving high temperature (e.g., 1350 °C) precrystallization, severe reduction (e.g., 700−1300 °C for up to 240 h in Ca or Ti metal vapor atmosphere), and postpurifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The material contained 4 × 10 20 e − cm −3 as determined by the titration method described by Yoshizumi et al, 47 comparable to the ones reported previously for C12A7 electride. 31,32 When loaded with 2 wt % Ru, the material catalyzed ammonia synthesis at a rate of 1.5 mmol ammonia g cat −1 h −1 in a mixture of 75% H 2 and 25% N 2 , at 633 K flowing at 30 cm 3 min −1 . The apparent activation energy of ammonia synthesis over the material was 72 kJ mol −1 (Figure S5), and ammonia synthesis was 0.7 order in N 2 pressure and 0.3 order in H 2 pressure under the conditions studied (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The material contained 4 × 10 20 e − cm −3 as determined by the titration method described by Yoshizumi et al, 47 comparable to the ones reported previously for C12A7 electride. 31,32 When loaded with 2 wt % Ru, the material catalyzed ammonia synthesis at a rate of 1.5 mmol ammonia g cat −1 h −1 in a mixture of 75% H 2 and 25% N 2 , at 633 K flowing at 30 cm 3 min −1 . The apparent activation energy of ammonia synthesis over the material was 72 kJ mol −1 (Figure S5), and ammonia synthesis was 0.7 order in N 2 pressure and 0.3 order in H 2 pressure under the conditions studied (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…The 12CaO•7Al 2 O 3 electride (C12A7:e − ) powders were synthesized via a one-step aluminothermic method directly from a mixture of commercially available CaO, Al 2 O 3 , and Al powders. 32 Calcium oxide (CaO, reagent grade), calcium carbonate (CaCO 3 , 99.5%), and gamma phase aluminum oxide (γ-Al 2 O 3 , 99.9%) are used as received from Alfa-Aesar. Aluminum (Al, reagent grade) powders are obtained from Fisher Scientific.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to studies by Khan et al, Salasin et al and Li et al showed the possibility to obtain electrides by synthesis from different Ca and Al precursor compounds and not the preformation of C12A7 [33][34][35][36][37][38] . A big step towards the batch synthesis of larger amounts of C12A7e -, in respect of an application as a catalyst support, was accomplished by Jiang et al by aluminothermic synthesis using a mixture of CaO, Al 2 O 3 and Al and heating under Ar at 1373 K for 8 h 39 . Besides challenges in the synthesis of the C12A7ematerial, its characterization and especially the determination of its electron concentration are not trivial.…”
Section: Introductionmentioning
confidence: 99%
“…Only for some special cases Raman spectroscopy, SQUID measurements are reported as ways to investigate the electron concentration 5,43 . Iodometric titration is also used frequently, however the role of metal impurities such as Al or Ca might influence the results as reported by Jiang et al 39,45 . Existing strategies for the synthesis of solid electrides reported in the literature mainly refer to bulk/batch synthesis and are thus limited in their scalability.…”
Section: Introductionmentioning
confidence: 99%